Magnetic resonance cholangiopancreatography study of pancreaticobiliary maljunction and pancreaticobiliary diseases - Wang, Cheng-Lin (World journal of gastroenterology : WJG, 2014)
AIM:To discuss the imaging anatomy about pancreaticobiliary ductal union,occurrence rate of pancreaticobiliary maljunction(PBM)and associated diseases in a Chinese population by using magnetic resonance cholangiopancreatography(MRCP).METHODS:Data were collected from 694 patients who underwent MRCP from January 2010 to December2012.Three hundred and ninety-three patients were male and 301 patients were female.The age range was16-92 years old and the average age was 51.8 years.The recruitment indication of all cases was patients who had clinical symptoms,such as abdominal pain,jaundice,nausea and vomiting,which thus were clinically suspected as relative pancreaticobiliary diseases.All cases were examined by MRCP using single-shot fast spin-echo sequences.In order to obtain MRCP images,the maximum intensity projection was used.RESULTS:According to the anatomy of pancreaticobiliary ductal union based on our analysis of MRCP images,all cases were classified into normal type and abnormal type according to the position of pancreaticobiliary ductal union.The abnormal type could be further divided into P-B type,B-P type and the duodenum type.By analyzing the incidence of biliary stone and inflammation,pancreatitis,biliary duct tumors and pancreatic tumors between normal and abnormal types,significant differences existed.The abnormal group was more likely to suffer from pancreaticobiliary diseases.Comparing three different types of PBM that were associated with pancreaticobiliary diseases by using Fisher’s method,the result showed that there was no significant difference in the incidence of biliary stones,cholecystitis and pancreatic tumors.The incidence of pancreatitis in B-P type and P-B type was higher than that in duodenum type;the incidence of biliary duct tumor in B-P type was higher than that in P-B type;the incidence of biliary duct tumor in duodenum type was lower than that in P-B type.The incidence of congenital choledochus dilatation in normal type and abnormal type was similar,and there was no significant difference between the two types.CONCLUSION:Types of PBM are closely related to the occurrence of pancreaticobiliary diseases.MRCP has important clinical value in the early diagnosis and preventive treatment of pancreaticobiliary diseases.